Staff Development Programs for Part-Time Occupational-Vocational Instructors An ERIC Brief - Lombardi, John, Comp.; ERIC Clearinghouse for Community Colleges ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
The lack of staff development, preservice, orientation, and inservice training programs for part-time community college instructors is considered a serious problem. This brief contains two examples of staff development programs for part-time vocational instructors. The first document, Dr. Milo P. Johnson's "Staff Development for Part-Time Vocational Instructors" is intended "to assist local continuing education and vocational education administrators in providing an up-to-date 'competency based' teacher education program as part of local staff development for part-time instructors." The second document describes the Maricopa County Community College District "Special Staff Development Program." It lists 13 learning units including a course on the community college. The Maricopa program was open to full-time and part-time instructors, and had a two-fold purpose: to enable full- and part-time instructors to qualify for Arizona certification; and to give instructors an overview of the characteristics of the adult learner and some learning principles applied to adults. In addition to an introductory essay documenting the need for staff development programs for part-time community college instructors, this brief includes a bibliography of related ERIC materials. (Author/NHM)
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
ERIC Note: Prepared for the Advisory Committee of the UCLA Community College Leadership Program.
Educational level discussed: Two Year Colleges.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bibliographies; College Faculty; Competency Based Teacher Education; Inservice Teacher Education; Part Time Faculty; Program Descriptions; Teacher Improvement; Teacher Orientation; Teachers; Two Year Colleges; Vocational Education Teachers; Staff Development Programs; Reports, Research